SARS‐CoV‐2 triggers complement activation through interactions with heparan sulfate. Issue 8 (18th August 2022) - Lo, Martin W; Amarilla, Alberto A; Lee, John D; Albornoz, Eduardo A; Modhiran, Naphak; Clark, Richard J; Ferro, Vito; Chhabra, Mohit; Khromykh, Alexander A; Watterson, Daniel; Woodruff, Trent M
Abstract: Objectives: To determine whether SARS‐CoV‐2 can trigger complement activation, the pathways that are involved and the functional significance of the resultant effect. Methods: SARS‐CoV‐2 was inoculated into a human lepirudin‐anticoagulated whole blood model, which contains a full repertoire of complement factors and leukocytes that express complement receptors. Complement activation was determined by measuring C5a production with an ELISA, and pretreatment with specific inhibitors was used to identify the pathways involved. The functional significance of this was then assessed by measuring markers of C5a signalling including leukocyte C5aR1 internalisation and CD11b upregulation with flow cytometry. Results: SARS‐CoV‐2 inoculation in this whole blood model caused progressive C5a production over 24 h, which was significantly reduced by inhibitors for factor B, C3, C5 and heparan sulfate. However, this phenomenon could not be replicated in cell‐free plasma, highlighting the requirement for cell surface interactions with heparan sulfate. Functional analysis of this phenomenon revealed that C5aR1 signalling and CD11b upregulation in granulocytes and monocytes was delayed and only occurred after 24 h. Conclusion: SARS‐CoV‐2 is a noncanonical alternative pathway activator that progressively triggers complement activation through interactions with heparan sulfate. Abstract : The mechanisms by which SARS‐CoV‐2 activates complement remain unclear, and so here, we utilised an ex vivo human whole blood model to interrogate the pathways and functional responses involved. SARS‐CoV‐2 inoculation in blood caused progressive C5a production over 24 h, which was blocked entirely by inhibitors for factor B, C3, C5 and heparan sulfate. This study therefore provides direct mechanistic evidence for SARS‐CoV‐2 driving complement activation and the requirement for cell surfaces and heparan sulfate.